Synthesis and application of high-stability bio-based plasticizer derived from ricinoleic acid. (15th April 2022) - Feng, Shan; Zhang, Pingbo; Jiang, Pingping; Zhang, Zheming; Deng, Jianneng; Cao, Zhiliang
Graphical abstract: The text overview diagram of synthesis and application of ricinoleic acid-derived high-stability bio-based plasticizer. The plasticizing mechanism of pure PVC and the PVC samples plasticized with A-ODL. Highlights: There is no article to test the migration of plasticizers in the refrigerator to simulate the stability of PVC in the cold storage, and this is the first one. Strong acid cation exchange resin can be used not only as a catalyst for epoxidation, but also as a ring opener for the following ring-opening acetylation reaction. The PVC plasticized by the ricinoleate bio-based plasticizers basically showed the minimal migration in various extreme environments. The PVC plasticized by the ricinoleate plasticizers exhibited an outstanding thermal stability. Abstract: As one of the most widely used plasticizers in the market, phthalate plasticizers have been banned in European countries and regions due to their poor migration and derived from petroleum-based raw materials. Therefore, using clean and renewable resources to produce high-stability bio-based environmentally friendly plasticizers is an urgent need currently. In this work, a new type of high-stability bio-based plasticizer was obtained by a four-step reaction with ricinoleic acid as main raw material, and its structure was characterized and identified by FT-IR and 1 H NMR. Subsequently, ricinoleate plasticizer, commercially available dioctyl phthalate (DOP), and bis(2-ethylhexyl) adipate (DOA) were added to prepare polyvinyl chloride (PVC) films for performance comparison. According to the TG results, the Ti (initial degradation temperature) of PVC films plasticized with ricinoleate plasticized was 40 ℃ higher than that of DOA and DOP. In addition, the tensile results showed that the ricinoleate could be used as a substitute for DOA, indicating its excellent plasticizing efficiency and mechanical properties. More importantly, ricinoleate plasticized PVC exhibited the ranking migration stability in various environments, lower glass transition temperature in DMA analysis. All the results demonstrated that compared with DOA and DOP, the ricinoleate has a better comprehensive performance, which provided a new way for the rational use of renewable resources to prepare environmentally friendly plasticizers.